Uterine Rupture at 35 Weeks Gestational Age after Laparoscopic Myomectomy- A Case Report (Global Journal of Medical Research, 2019)
Laparoscopic myomectomy is a treatment option to preserve fertility and alleviate symptoms associated with fibroids. Although this procedure is reasonably expected to increase the risk of uterine rupture during pregnancy, reports on this issue are scarce. We are, hereby, reporting a case of second gravida who conceived within 2 months of laparoscopic myomectomy who presented with complaints of pain abdomen and decreased fetal movements at 35 weeks of gestational age. She was found to be in early shock with her abdomen tense and tender and was taken up for emergency cesarean section promptly. Every abdominal pain in pregnant women with scarred uterus should be carefully evaluated and properly examined to rule out rupture. Proper advice to the patients regarding the risks during pregnancy post myomectomy is a must.